Analysis of a Physical Layer Security Solution with Channel Estimation - Estela-Zamora, M; Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2024)
Physical layer security has emerged in the last years as a field of interest for the development of new methods and techniques to achieve higher security in wireless networks. Many solutions have been proposed and a lot of metrics have been used for sizing the system s confidentiality, such as the secrecy capacity and secrecy rate. This paper aims to contribute to physical layer security development through the analysis of a theoretical model, already existing and selected by a previous analysis of several works, in order to dimension how the secrecy capacity and secrecy rate can be affected by the availability and accuracy of the channel state information, determined through channel estimation techniques. © 2024 IEEE.